Counting Degrons: Lessons From Multivalent Substrates for Targeted Protein Degradation - Okoye, Cynthia N.; Rowling, Pamela J. E.; Itzhaki, Laura S.; Lindon, Catherine (Frontiers in Physiology, 2022)
E3s comprise a structurally diverse group of at least 800 members, most of which target multiple substrates through specific and regulated protein-protein interactions. These interactions typically rely on short linear motifs (SLiMs), called “degrons”, in an intrinsically disordered region (IDR) of the substrate, with variable rules of engagement governing different E3-docking events. These rules of engagement are of importance to the field of targeted protein degradation (TPD), where substrate ubiquitination and destruction require tools to effectively harness ubiquitin ligases (E3s). Substrates are often found to contain multiple degrons, or multiple copies of a degron, contributing to the affinity and selectivity of the substrate for its E3. One important paradigm for E3-substrate docking is presented by the Anaphase-Promoting Complex/Cyclosome (APC/C), a multi-subunit E3 ligase that targets hundreds of proteins for destruction during mitotic exit. APC/C substrate targeting takes place in an ordered manner thought to depend on tightly regulated interactions of substrates, with docking sites provided by the substoichiometric APC/C substrate adaptors and coactivators, Cdc20 or Cdh1/FZR1. Both structural and functional studies of individual APC/C substrates indicate that productive ubiquitination usually requires more than one degron, and that degrons are of different types docking to distinct sites on the coactivators. However, the dynamic nature of APC/C substrate recruitment, and the influence of multiple degrons, remains poorly understood. Here we review the significance of multiple degrons in a number of E3-substrate interactions that have been studied in detail, illustrating distinct kinetic effects of multivalency and allovalency, before addressing the role of multiple degrons in APC/C substrates, key to understanding ordered substrate destruction by APC/C. Lastly, we consider how lessons learnt from these studies can be applied in the design of TPD tools.